Availability of equipment and medications for non-communicable diseases and injuries at public first-referral level hospitals: a cross-sectional analysis of service provision assessments in eight low-income countries. Issue 10 (10th October 2020) - Gupta, Neil; Coates, Matthew M; Bekele, Abebe; Dupuy, Roodney; Fénelon, Darius Leopold; Gage, Anna D; Getachew, Theodros; Karmacharya, Biraj Man; Kwan, Gene F; Lulebo, Aimée M; Masiye, Jones K; Mayige, Mary Theodory; et al.
Abstract : Context and objectives: Non-communicable diseases and injuries (NCDIs) comprise a large share of mortality and morbidity in low-income countries (LICs), many of which occur earlier in life and with greater severity than in higher income settings. Our objective was to assess availability of essential equipment and medications required for a broad range of acute and chronic NCDI conditions. Design: Secondary analysis of existing cross-sectional survey data. Setting: We used data from Service Provision Assessment surveys in Bangladesh, the Democratic Republic of the Congo, Ethiopia, Haiti, Malawi, Nepal, Senegal and Tanzania, focusing on public first-referral level hospitals in each country. Outcome measures: We defined sets of equipment and medications required for diagnosis and management of four acute and nine chronic NCDI conditions and determined availability of these items at the health facilities. Results: Overall, 797 hospitals were included. Medication and equipment availability was highest for acute epilepsy (country estimates ranging from 40% to 95%) and stage 1–2 hypertension (28%–83%). Availability was low for type 1 diabetes (1%–70%), type 2 diabetes (3%–57%), asthma (0%–7%) and acute presentations of diabetes (0%–26%) and asthma (0%–4%). Few hospitals had equipment or medications for heart failure (0%–32%), rheumatic heart disease (0%–23%), hypertensive emergencies (0%–64%) or acute minor surgical conditions (0%–5%). Data for chronic pain were limited to only two countries. Availability of essential medications and equipment was lower than previous facility-reported service availability. Conclusions: Our findings demonstrate low availability of essential equipment and medications for diverse NCDIs at first-referral level hospitals in eight LICs. There is a need for decentralisation and integration of NCDI services in existing care platforms and improved assessment and monitoring to fully achieve universal health coverage.